Study the effect of lactoperoxidase activation in combination with heat treatment or nisin on the microbiological quality of raw milk - Chedia Aouadhi; Souhir Kmiha; Faten Trakhna; Abderrazak Maaroufi (Applied Food Research)
The aim of the current study was to improve the microbiological quality of raw cow milk by activating the lactoperoxidase system using either nisin or heat treatment. A central composite experimental design with three factors was used to evaluate the effect of thiocyanate (SCN), hydrogen peroxide (H202) and nisin on the microbiological quality of raw milk. The experimental response was measured in terms of the logarithmic reduction in total microbial, total coliforms count, yeasts and molds. Our results indicate that the combination of both treatments was highly effective in destroying various microorganisms. In fact, the optimal values of each parameter (SCN, H202 and nisin) for a 6log, 5log and 4log reductions of the initial number of total aerobic mesophilic bacteria, coliforms, yeasts and molds were around 7 mg/L of SCN, 15 mg/L of H202 and 50 IU/mL of nisin, obtained after 72 h of incubation at 25 °C. Concerning the LPS activation at moderate temperature, our data suggest that this combination was very effective in destroying different microorganisms. Certainly, the total destruction of coliforms, yeasts and molds was noted after 96 h incubation at 25 °C after LPS activation for 4 h and 6 h followed by heat treatment (63 °C for 30 min). These results highlight a synergistic effect between the LPS activation and nisin or heat treatment in preserving microbiological quality of raw milk for 72 h or 96 h at 25 °C, respectively. Such treatments could be implemented by the dairy industry to enhance the quality of fresh milk and consequently of dairy products.